Modern romance - Ansari, Aziz 1983- (Penguin Press, 2015)
The acclaimed comedian teams up with a New York University sociologist to explore the nature of modern relationships, evaluating how technology is shaping contemporary relationships and considering the differences between courtships of the past and present